2022
DOI: 10.1213/ane.0000000000005829
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Health Literacy and Enhanced Recovery After Surgery Protocol Adherence and Postoperative Outcomes Among Patients Undergoing Colorectal Cancer Surgery: A Prospective Cohort Study

Abstract: BACKGROUND: Low health literacy (HL) adversely affects medical adherence and health outcomes in patients with chronic diseases. However, the association between HL and enhanced recovery after surgery (ERAS) adherence and postoperative outcomes has not been investigated in patients undergoing colorectal surgery. METHODS: The data of all patients from a single academic institution who underwent colorectal surgery on an ERAS pathway from January 2019 to July 2020 were prospectively collected. HL levels were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(69 reference statements)
2
4
0
Order By: Relevance
“…2 Furthermore, among 240 propensity-matched pairs of colorectal patients with low and adequate health literacy (based on BHLS scores), respectively, Qin et al demonstrated adequate health literacy to be significantly associated with higher adherence to multiple ERP components including preoperative optimization (90.8% vs. 71.7%; adjusted p < 0.001), early feeding (59.2% vs. 31.3%; adjusted p < 0.001), and early mobilization (56.7% vs. 30.4%; adjusted p < 0.001). 76 Additionally, in keeping with findings from Thiess et al, 2 low health literacy was associated with significantly higher incidence of postoperative complications (32.1% vs. 20.8%, p < 0 0.01). 76…”
Section: Future Worksupporting
confidence: 77%
See 3 more Smart Citations
“…2 Furthermore, among 240 propensity-matched pairs of colorectal patients with low and adequate health literacy (based on BHLS scores), respectively, Qin et al demonstrated adequate health literacy to be significantly associated with higher adherence to multiple ERP components including preoperative optimization (90.8% vs. 71.7%; adjusted p < 0.001), early feeding (59.2% vs. 31.3%; adjusted p < 0.001), and early mobilization (56.7% vs. 30.4%; adjusted p < 0.001). 76 Additionally, in keeping with findings from Thiess et al, 2 low health literacy was associated with significantly higher incidence of postoperative complications (32.1% vs. 20.8%, p < 0 0.01). 76…”
Section: Future Worksupporting
confidence: 77%
“…76 Additionally, in keeping with findings from Thiess et al, 2 low health literacy was associated with significantly higher incidence of postoperative complications (32.1% vs. 20.8%, p < 0 0.01). 76…”
Section: Future Worksupporting
confidence: 77%
See 2 more Smart Citations
“…China’s research shows that the health expenditure in eastern and urban areas is higher, which may be because the medical and health resources and professionals in eastern and urban areas are more abundant than those in central areas and rural areas, providing more convenient and comprehensive health services; thus, the medical costs are higher [ 10 ]. The improvement of education level will improve people’s health awareness and make them more willing to pay more for health expenditure [ 17 ], which is consistent with the reason that people with high health literacy pay more attention to health promotion [ 18 ]. Self-medication belongs to the scope of public behavioral decision making, and personality traits can also influence public behavioral decision making [ 19 ].…”
Section: Introductionmentioning
confidence: 77%